Exploring philosophy - "Cahn, Steven M. (ed.)" (New York, 2000)
Exploring Philosophy: An Introductory Anthology is a remarkably accessible and inviting introduction to philosophy. In this unique volume Steven M. Cahn brings together extraordinarily clear recent essays by noted philosophers and supplements them with influential historical sources. Most importantly, the articles have been carefully edited to make them understandable to every reader. The topics are drawn from the major fields of philosophy and include knowledge and skepticism, freedom and determinism, mind and body, the existence of God, the problem of evil, faith and reason, cultural relativism, abortion, euthanasia, democracy, privacy, capital punishment, affirmative action, death, and the meaning of life. The collection also contains, in preeminent translations and with explanatory notes, the complete texts of Plato's Meno, Euthyphro, Apology, and Crito as well as specially selected materials by Aristotle, Aquinas, Descartes, Hume, Kant, and Mill. Also provided are an introduction to logic and scientific method and guiding commentary by the editor. Exploring Philosophy: An Introductory Anthology is a landmark collection that enables all readers to appreciate for themselves the importance and fascination of philosophical inquiry.
Keywords: Philosophy introductions-Anthology